Robots and sensor clouds - Koubâa, Anis; Shakshuki, Elhadi (Springer, 2016)
This book comprises four chapters that address some of the latest research in clouds robotics and sensor clouds. The first part of the book includes two chapters on cloud robotics. The first chapter introduces a novel resource allocation framework for cloud robotics and proposes a Stackelberg game model and the corresponding task oriented pricing mechanism for resource allocation. In the second chapter, the authors apply Cloud Computing for building a Cloud-Based 3D Point Cloud extractor for stereo images. Their objective is to have a dynamically scalable and applicable to near real-time scenarios.- Resumé vydavatel
Keywords: internet věcí; bezdrátové senzorové sítě; robotika; Internet of things; wireless sensor networks; robotics; electronic books; monographs; monografie; elektronické knihy